(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Given the scarcity of water and the decline in non-renewable groundwater levels in the regions where palm cultivation is concentrated, this study aims to measure the impact of achieving self-sufficiency and net exports on the water used in date production, as well as its share of total agricultural water consumption, using economic equations and econometric analysis. The study indicates an increase in both the self-sufficiency ratio and Saudi net exports of dates, with annual growth rates of 0.6% and 10.4%, respectively, during the period 2000–2023. The total cumulative volume of water used to achieve self-sufficiency in dates reached 32.52 billion m³ representing 91.76%, while the cumulative virtual water used for net exports did not exceed 8.7% of the cumulative water used in date production by the end of the period 2000–2023. Water requirements for achieving self-sufficiency are expected to rise from 2.16 billion m³ in 2024 to 2.73 billion m³ in 2030. Similarly, the amount of water required for Saudi net exports of dates is projected to increase from 252.08 million m³ in 2024 to 380.63 million m³ in 2030. The total water used in date production is also expected to increase from 2.42 billion m³ in 2024 to 3.11 billion m³ in 2030, while the share of water allocated to date production out of total agricultural water use is forecast to rise from 15.99% in 2024 to 21.07% in 2030. To achieve the objective of rationalizing water consumption and preventing the depletion of groundwater in sedimentary-shelf regions, the study recommends maintaining the current cultivated area of date palms, limiting tree replacement to high-quality varieties only, and reconsidering the policy of exporting dates abroad.